1993
DOI: 10.1073/pnas.90.21.10315
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta effects on expression of G1 cyclins and cyclin-dependent protein kinases.

Abstract: Transforming growth factor (31 (TGF-f81) is a potent growth-inhibitory polypeptide. The mechanism of TGF-13, inhibition has been related to its ability to prevent the hyperphosphorylation of retinoblastoma protein (pRb). Several lines of evidence have suggested that cell cycle-regulated protein kinases are responsible for the hyperphosphorylation of pRb. We demonstrate here that TGF-fi1 has profound effects on the expression of genes encoding certain Gl cyclins and their associated kinases, which provides one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
128
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(140 citation statements)
references
References 32 publications
(36 reference statements)
9
128
1
2
Order By: Relevance
“…However, these studies did not evaluate the effect of tamoxifen on the cell cycle machinery. The period of responsiveness to tamoxifen in G 1 is reminiscent of the effects of transforming growth factor ␤ (TGF-␤) on cell cycle advance, which are known to involve primarily a blockage of pRb phosphorylation (14,25). Thus, after cells have phosphorylated their complement of pRb in late G 1 , they become nonresponsive to the growth-inhibitory effects of TGF-␤.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies did not evaluate the effect of tamoxifen on the cell cycle machinery. The period of responsiveness to tamoxifen in G 1 is reminiscent of the effects of transforming growth factor ␤ (TGF-␤) on cell cycle advance, which are known to involve primarily a blockage of pRb phosphorylation (14,25). Thus, after cells have phosphorylated their complement of pRb in late G 1 , they become nonresponsive to the growth-inhibitory effects of TGF-␤.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies demonstrated that SRF was overabundant and highly active in epithelial tumor cells that had undergone mesenchymal transition (Geng and Weinberg, 1993). The elevated SRF DNA-binding activity correlated with the increased expression of SRF itself, and with actin and vinculin, which are both SRFdependent genes.…”
Section: Discussionmentioning
confidence: 98%
“…This effect is mediated by several events that are activated downstream of the TGF-b receptor. This includes the transcriptional repression of the proto-oncogene c-myc (Alexandrow et al, 1995), downmodulation of the expression and activities of G1 and G2 CDK and cyclins (Ewen et al, 1993;Geng and Weinberg, 1993;Iavarone and Massague, 1997), and activation of the genes encoding p15 INK4b (Hannon and Beach, 1994), p21 Cip1 (Datto et al, 1995;Claassen and Hann, 2000) and p27 Kip1 (Polyak et al, 1994;Depoortere et al, 2000) that encode CDK inhibitors. Previously, it was demonstrated that Smads functionally cooperate with Sp1 to activate the human p21 Cip1 and p15 INK4b promoters.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CDK2 regulation has been studied mainly at post translational level (13), and only a few reports have discussed the oscillation of CDK2 levels before S-phase entry (14,15). This suggests that the regulation of CDK2 at the transcriptional level could be as important as its post-translational control.…”
mentioning
confidence: 99%